Exploration and verification of the therapeutic mechanism of shenfu injection in sepsis-induced myocardial injury. - Hua-Jing Yuan; Guo-Han Xiang; Yang Liu; Yan Li; Wen-Li Liu; Jiu-Xiang Wei; Yi-Tao Xue; Hao Hao (PLoS ONE)
Background Shenfu injection (SFI), derived from a traditional Chinese medicine (TCM) prescription, is an effective drug for the treatment of sepsis-induced myocardial injury (SIMI) with good efficacy, but its exact therapeutic mechanism remains unclear. Methods SwissTargetPrediction and GeneCards database were used to obtain relevant targets for SFI and SIMI. STRING 11.5 and MCODE were used to analyse potential therapeutic targets for SFI. DAVID 6.8 database was used to perform enrichment analysis. In addition, the SIMI model was constructed by cecal ligation and puncture (CLP) on Sprague Dawley rats and the related protein expression levels were verified by AutoDock Vina 1.1.2 and experiment. Results SFI has a total of 10 main active compounds and treats SIMI through 52 potential targets, among which LGALS3, STAT3, FGF1, and AKT1 were the core targets for treatment. Based on enrichment analysis, STAT3, FGF1, and AKT1 in the core targets were experimentally validated. The experimental results showed that SFI effectively ameliorated the inflammatory response and myocardial injury and inhibited apoptosis in SIMI. And SFI improved SIMI by decreasing caspase-9, STAT3 and phospho-AKT1 (p-AKT1) expression, and enhancing FGF1 expressions. Conclusions This study showed that SFI effectively reduced the expression of caspase-9, STAT3 and p-AKT1, enhanced the expression of FGF1, reduced the inflammatory response, inhibited apoptosis and attenuated cardiac injury to SIMI.